2010
DOI: 10.1007/s00125-010-1705-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of glucose control in patients with chronic pancreatitis

Abstract: Aims/hypothesis Diabetes frequently develops in patients with chronic pancreatitis (CP). Partial pancreatectomy has emerged as a treatment option for such patients. We addressed whether the development of diabetes in CP patients is related to pancreatic beta cell area or clinical variables, and which factors predict the diabetes risk after partial pancreatectomy. Methods Fractional beta cell area was determined in pancreatic tissue samples obtained from 114 CP patients undergoing pancreatic surgery and related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
3
18
0
7
Order By: Relevance
“…Thus, the curve-linear relationship between pancreatic beta cell area and fasting glucose concentrations was shifted upwards by~0.44 mmol/l (8 mg/dl) in individuals with the lowest insulin sensitivity compared with the most insulin-sensitive individuals. This is consistent with previous studies showing that a modest increase in BMI confers a greater risk for developing diabetes after a partial pancreatectomy even in a predominantly lean population of patients with chronic pancreatitis [6]. Interestingly, the degree of insulin sensitivity appeared to be less important for the 120 min post-challenge glucose concentrations, indicating that the glycaemic response to the oral glucose load was primarily determined by the extent of pancreatic beta cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the curve-linear relationship between pancreatic beta cell area and fasting glucose concentrations was shifted upwards by~0.44 mmol/l (8 mg/dl) in individuals with the lowest insulin sensitivity compared with the most insulin-sensitive individuals. This is consistent with previous studies showing that a modest increase in BMI confers a greater risk for developing diabetes after a partial pancreatectomy even in a predominantly lean population of patients with chronic pancreatitis [6]. Interestingly, the degree of insulin sensitivity appeared to be less important for the 120 min post-challenge glucose concentrations, indicating that the glycaemic response to the oral glucose load was primarily determined by the extent of pancreatic beta cells.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, the manifestation of diabetes in lean patients without a typical history of type 2 diabetes has been considered as a clinical indication of pancreatic carcinoma [4]. At present, studies on the pathogenesis of pancreatic diabetes in humans are relatively sparse, but progressive beta cell destruction is held to be the major underlying cause [5,6]. Whether insulin resistance is involved in the development of diabetes in such patients is not known, given the paucity of studies in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 In all, 17 studies were included in the final set (Table 1). [14][15][16][17][21][22][23][24][83][84][85][86][87][88][89][90][91] All primary studies reported retrospective analyses of prospectively maintained databases, suggesting that selection bias may exist in this body of literature. Our 17 study cohort included a total of 4,045 patients, though BMI information was reported heterogeneously.…”
Section: Study Populationmentioning
confidence: 99%
“…Brittle diabetes is also frequently developed in patients with chronic pancreatitis after partial pancreatectomy and its development is partially related to reduced pancreatic beta-cell area , as well as other clinical variables, i.e. pre-operative fasting glucose levels, HbA1c and body mass index (Schrader et al, 2010). This is further highlighted by the fact that different surgical procedures have an unequal impact on glucose control.…”
Section: Aetiology and Pathophysiologic Substrate: From The Suspicionmentioning
confidence: 99%